Engineering a controllable and reversible switch for CAR-based cellular immunotherapies via a genetic code expansion system - Yue Liu; Lingna An; Xiaoqi Wang; Yueyu Dai; Cheng Zhang; Qin Wen; Xi Zhang (Journal of Hematology & Oncology)
Abstract Background As one of the most promising adoptive cell therapies, CAR-T cell therapy has achieved notable clinical effects in patients with hematological tumors. However, several treatment-related obstacles remain in CAR-T therapy, such as cytokine release syndrome, neurotoxicity, and high-frequency recurrence, which severely limit the long-term effects and can potentially be fatal. Therefore, strategies to increase the controllability and safety of CAR-T therapy are urgently needed. Methods In this study, we engineered a genetic code expansion-based therapeutic system to achieve rapid CAR protein expression and regulation in response to cognate unnatural amino acids at the translational level. When the unnatural amino acid N-ε-((tert-butoxy) carbonyl)-l-lysine (BOCK) is absent, the CAR protein cannot be completely translated, and CAR-T is “closed”. When BOCK is present, complete translation of the CAR protein is induced, and CAR-T is “open”. Therefore, we investigated whether the BOCK-induced device can control CAR protein expression and regulate CAR-T cell function using a series of in vitro and in vivo experiments. Results First, we verified that the BOCK-induced genetic code expansion system enables the regulation of protein expression as a controllable switch. We subsequently demonstrated that when the system was combined with CAR-T cells, BOCK could effectively and precisely control CAR protein expression and induce CAR signaling activation. When incubated with tumor cells, BOCK regulated CAR-T cells cytotoxicity in a dose-dependent manner. Our results revealed that the presence of BOCK enables the activation of CAR-T cells with strong anti-tumor cytotoxicity in a NOG mouse model. Furthermore, we verified that the BOCK-induced CAR device provided NK cells with controllable anti-tumor activity, which confirmed the universality of this device. Conclusions Our study systematically demonstrated that the BOCK-induced genetic code expansion system effectively and precisely regulates CAR protein expression and controls CAR-T cell anti-tumor effects in vitro and in vivo. We conclude that this controllable and reversible switch has the potential for more effective, secure, and clinically available CAR-based cellular immunotherapies.